How Tumor Cells Choose Between Epithelial-Mesenchymal Transition and Autophagy to Resist Stress—Therapeutic Implications - Marcucci, Fabrizio; Rumio, Cristiano (Frontiers in Pharmacology, 2018)
Tumor cells undergo epithelial-mesenchymal transition (EMT) or macroautophagy (hereafter autophagy) in response to stressors from the microenvironment. EMT ensues when stressors act on tumor cells in the presence of nutrient sufficiency, and mechanistic target of rapamycin (mTOR) appears to be the crucial signaling node for EMT induction. Autophagy, on the other hand, is induced in the presence of nutrient deprivation and/or stressors from the microenvironment with 5' adenosine monophosphate-activated protein kinase (AMPK) playing an important, but not exclusive role, in autophagy induction. Importantly, mTOR and EMT on one hand, and AMPK and autophagy on the other hand, negatively regulate each other. Such regulation occurs at different levels and suggests that, in many instances, these two stress responses are mutually exclusive. Nevertheless, EMT and autophagy are able to interconvert and we suggest that this may depend on spatiotemporal changes in the tumor microenvironment and/or on duration/intensity of the stressor signal(s). Eventually, we propose a three-pronged therapeutic approach aimed at targeting these three major tumor cell populations. First, cytotoxic drugs that act on differentiated and proliferating tumor cells and which, per se, may promote induction of EMT or autophagy in surviving tumor cells. Second, inhibitors of mTOR in order to prevent EMT induction. Third inducers of autophagic cell death (autosis) in order to deplete tumor cells that are constitutively in an autophagic state or are induced to enter an autophagic state in response to antitumor therapy.